Climate change favours connectivity between virus-bearing pest and rice cultivations in sub-Saharan Africa, depressing local economies - Mattia Iannella (PeerJ Inc., 2021)
Aims Rice is a staple food for many countries, being fundamental for a large part of the worlds’ population. In sub-Saharan Africa, its importance is currently high and is likely to become even more relevant, considering that the number of people and the per-capita consumption are both predicted to increase. The flea beetles belonging to the Chaetocnema pulla species group (pulla group), a harmful rice pest, are an important vector of the Rice Yellow Mottle Virus, a disease which leads even to 80–100% yield losses in rice production. We present a continental-scale study aiming at: (1) locating current and future suitable territories for both pulla group and rice; (2) identifying areas where rice cultivations may occur without suffering the presence of pulla group using an Ecological Niche Modelling (ENM) approach; (3) estimating current and future connectivity among pulla group populations and areas predicted to host rice cultivations, based on the most recent land-use estimates for future agricultural trends; (4) proposing a new connectivity index called “Pest Aggression Index” (PAI) to measure the agricultural susceptibility to the potential future invasions of pests and disease; (5) quantifying losses in terms of production when rice cultivations co‐occur with the pulla group and identifying the SSA countries which, in the future inferred scenarios, will potentially suffer the greatest losses. Location Sub-Saharan Africa. Methods Since the ongoing climate and land-use changes affect species’ distributions, we first assess the impact of these changes through a spatially-jackknifed Maxent-based Ecological Niche Modelling in GIS environment, for both the pulla group and rice, in two climatic/socioeconomic future scenarios (SSP_2.45 and 3.70). We then assess the connectivity potential of the pulla group populations towards rice cultivations, for both current and future predictions, through a circuit theory-based approach (Circuitscape implemented in Julia language). We finally measure the rice production and GPD loss per country through the spatial index named “Pest Aggression Index”, based on the inferred connectivity magnitude. Results The most considerable losses in rice production are observed for Liberia, Sierra Leone and Madagascar in all future scenarios (2030, 2050, 2070). The future economic cost, calculated as USD lost from rice losses/country’s GDP results are high for Central African Republic (−0.6% in SSP_2.45 and −3.0% in SSP_3.70) and Guinea–Bissau (−0.4% in SSP_2.45 and −0.68% in SSP_3.70), with relevant losses also obtained for other countries. Main conclusions Since our results are spatially explicit and focused on each country, we encourage careful land-use planning. Our findings could support best practices to avoid the future settlement of new cultivations in territories where rice would be attacked by pulla group and the virus, bringing economic and biodiversity losses.